Construction of an Integrated Positive Youth Development Conceptual Framework for the Prevention of the Use of Psychotropic Drugs among Adolescents - Tak Yan Lee (The Scientific World Journal)
This is a theoretical paper with an aim to construct an integrated conceptual framework for the prevention of adolescents' use and abuse of psychotropic drugs. This paper first reports the subjective reasons for adolescents' drug use and abuse in Hong Kong and reviews the theoretical underpinnings. Theories of drug use and abuse, including neurological, pharmacological, genetic predisposition, psychological, and sociological theories, were reviewed. It provides a critical re-examination of crucial factors that support the construction of a conceptual framework for primary prevention of adolescents' drug use and abuse building on, with minor revision, the model of victimization and substance abuse among women presented by Logan et al. This revised model provides a comprehensive and coherent framework synthesized from theories of drug abuse. This paper then provides empirical support for integrating a positive youth development perspective in the revised model. It further explains how the 15 empirically sound constructs identified by Catalano et al. and used in a positive youth development program, the Project P.A.T.H.S., relate generally to the components of the revised model to formulate an integrated positive youth development conceptual framework for primary prevention of adolescent drug use. Theoretical and practical implications as well as limitations and recommendations are discussed.